Users Joining Multiple Sites: Distributions and Patterns - Zafarani, Reza; Liu, Huan (Proceedings of the International AAAI Conference on Web and Social Media, 2014)
The rise of social media has led to an explosion in the number of possible sites users can join. However, this same profusion of social media sites has made it nearly impossible for users to actively engage in all of them simultaneously. Accordingly, users must make choices about which sites to use or to neglect. In this paper, we study users that have joined multiple sites. We study how individuals are distributed across sites, the way they select sites to join, and behavioral patterns they exhibit while selecting sites. Our study demonstrates that while users have a tendency to join the most popular or trendiest sites, this does not fully explain users' selections. We demonstrate that peer pressure also influences the decisions users make about joining emerging sites.